The use of FAC-1 as a contractual integrator enhancing the use of BIM: a focus on the Liscate school in Italy - Ettore Giana, Paolo (2020)
This paper reflects on the capacities of enterprise contracts, such as the ‘FAC-1 Framework Alliance Contract’, to facilitate and enhance the success of BIM processes. We will consider some of the main legal issues arising in the development of a project using BIM processes and will show how the application of FAC-1 as a collaborative framework helped tackle such legal issues on a school project undertaken in the municipality of Liscate in Italy. We will highlight how, on the Liscate project, the correct combination of a collaborative contract tool, a good procurement strategy and the adoption of BIM increased the efficiency of information exchanges, the effectiveness of process decisions and information management and the reduction of information asymmetries.